(untitled) (Global Journal of Science Frontier Research, 2020)
The electronic structure of homogeneous and inhomogeneous quantum dots involves fascinating optoelectronic properties. Herein, a detailed theoretical and numerical investigation of the electronic structure of spherical inhomogeneous quantum dots InN/In x Ga 1-x N/Ligand, based Indium and Gallium Nitride, with a variable composition x of Indium. A more real profile is adopted with a finite potential shell and variable thickness. The ligand and solution impose external confinement. With such shell In x Ga 1-x N, a minimum of defects is ensured at the interface, and the structure is passivated. Along with this work, we will explore the effects of the various parameters of this nanosystem on its gap, on the location of charge carriers and the distribution of nS-nP energy levels. We will show how the dimensions of the material core InN, the material shell In x Ga 1-x N, and the Indium-composition x control the characteristics of the nanosystem and consequently improve the electronic and optical properties. Then a detailed calculation of the electronic structure will be made.